(untitled) (Journal of Philosophy Culture and Political Science, 2022)
The long-lasting conflict in Afghanistan leads to an aggravation of the socio-economic crisis in the country. This is a serious obstacle to the stable development of Afghan society and a challenge to regional security. The peace talks in Qatar in September 2020 between the Government of the IRA and the Taliban movement could contribute to ending the conflict and implementing measures for the peaceful construction and development of the country. However, the events following the announcement of the withdrawal of international forces from Afghanistan and the coming to power of the Taliban government have once again put on the agenda the issue of finding ways to resolve the conflict as soon as possible by peaceful means. The article analyzes the fundamental principles of establishing the peace process in Afghanistan. Exploring the interaction of all parties involved in the peace process, the authors pose research questions: "What are the main difficulties in establishing a peace process in Afghanistan?" and “is there a prospect of achieving peace and stability in modern Afghanistan?" The role of national, regional and international actors in establishing peace in Afghanistan is considered based on the content-analysis and review of the opinion of the expert community (using the Delphi method), as well as their own observations (the included observation method) of one of the authors of the article, who was a direct participant in the Doha negotiation process. Key words: Peacebuilding, nation building, stability, US Military withdrawal, Afghanistan